IoT-enabled Health Monitoring: Technological Perspectives in Clinical Nutrition (International Journal of Food and Nutritional Sciences, 2022)
Internet of Things (IoT) technology has changed healthcare, especially clinical nutrition. This study examines IoT-enabled health monitoring methods in clinical nutrition from a technology standpoint. Wearable devices with biometric sensors, smart kitchen appliances with nutrient analysis, mobile health apps, advanced data analytics, machine learning, remote patient monitoring, and an IoT-enabled Wearable Nutrient Tracker System are examined. The evaluation considers accuracy, user compliance, privacy and security, cost and accessibility, and application breadth. From vital sign monitoring to real-time nutrient analysis and remote patient support, each method has pros and cons. These technologies promise to give individualized and actionable nutritional insights for proactive heath management.To make educated healthcare decisions, the research emphasizes a detailed comprehension of various strategies. The conclusion covers the wide ecosystem of IoT-enabled health monitoring technologies and forecasts continuous advances that will solve present constraints, enabling more effective tools for individualized clinical nutrition monitoring. This study advances healthcare IoT and provides insights for researchers, healthcare professionals, and technology developers seeking to improve clinical nutrition patient outcomes.